A mathematical model of self-organisation in football. (4th March 2018) - Chassy, Philippe; Malone, James J.; Clark, Dan P. A.
Abstract: The theory of self-organising systems was used to analyse the factors that play a key role in a football teams' performance. The resulting mathematical model revealed that passing was the most central component to team's performance. The current study aimed to introduce a spatial component into the model by exploring passing data from different spatial zones of the pitch (defence, midfield and attack). This analysis helped understand the organisation which underpins the dynamics at the core of team performance when in possession of the ball. The amended Spatial Integrated Model of Self-Organisation in Football Teams (SIMSOFT) considers seven parameters of which six relate to passing frequency and accuracy. SIMSOFT outputs a team play index which, when applied to the results from Barclays Premier League on the complete 760 games of season 2012–2013, accounts for 57% of the variance in football team performance, measured as the number of goals scored per minute of possession. We conclude that the self-organising theoretical framework is a useful theoretical approach to examine the performance of football teams. These findings may have potential implications for coaches' looking to develop footballers in the most efficient way to maximise performance outcome.